Consequences and resilience of tourism to the impact of the pandemic from a local management perspective for the case of Malaga - Nuevo-López, Abraham; Martínez del Vas, Ginesa; Puig-Cabrera, Miguel (Revista de Estudios Andaluces, 2023)
This article explores the impact of the COVID-19 pandemic on the tourism sector in the city of Malaga. The main objective of the study is to analyse the effects that the pandemic has had, as well as the responses that have been given to rebuild the tourism system in the city of Malaga. The study uses a qualitative and descriptive methodology, prioritising the search for primary sources (institutional) to measure the impact of the pandemic on tourism in Malaga. There are two main conclusions of the study: firstly, the Malaga tourism industry has shown such a level of dynamism and resilience that it has been able to initiate a slow but vigorous recovery of the tourism productive fabric; secondly, the actions of the public administrations have generally been diligent, efficient, rapid, and flexible, although the level of interpenetration and synergy between public administrations, tourism operators and residents is still insufficient.